Simulating natural hydrate formation and accumulation in sediments from dissolved methane using a large three-dimensional simulator. (15th March 2018) - Li, Nan; Sun, Zhen-Feng; Sun, Chang-Yu; Li, Peng; Chen, Guang-Jin; Ma, Qing-Lan; Liu, Bei
Highlights: Slow hydrate formation and accumulation process from dissolved gas in nature was simulated. A dynamic hydrate evolution process exists: crystallization – migration – accumulation – recrystallization. The final morphologies in pores are stiff frame supporting hydrate and patchy hydrate. Hydrate saturation was inversed from resistivity and acoustic velocity for frame supporting hydrate. Field of concentration, temperature and fluid velocity play key role on the discontinuity of hydrate distribution. Abstract: The slow hydrate formation and accumulation process from dissolved gas in nature was simulated at large-scale in sandy sediments using a three-dimensional hydrate simulator. A low hydrate formation rate (0.37% pore volume per day) was achieved by maintaining the supersaturation of dissolved methane and migration velocity of the pore fluid at very low levels. Electrical and acoustic measurements were performed to track the hydrate formation in the sediments. A dynamic hydrate evolution process was observed: Crystallization – migration – accumulation – recrystallization. This evolution process has a critical effect on the connectivity of the pores and the strength of the sediment frame. After the dynamic evolution process, stiff frame-supporting hydrates and patchy hydrates were observed as the final morphologies in the pores, although the variation in the acoustic velocity indicated that frame supporting was the dominating morphology in the pores. Based on this, hydrate saturation values were inversed from resistivity and acoustic velocity models for frame-supporting hydrates. The calculated results showed that the order of hydrate saturation at different sites from the resistivity model was consistent with that from the acoustic velocity model by overestimating the hydrate saturation obtained from the resistivity inversion. Analysis of the spatial hydrate distribution showed that hydrate distribution in the sediments was discontinuous. The concentration, temperature, and fluid velocity profiles play a key role on this discontinuity, which we propose should be considered in detail in future experimental and numerical studies.